Landsvirkjun cost estimating and assessment for small hydropower plants : methodology and basis for estimating cost - Viðar Helgason (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri This research is in the field of Project Management and it examines the process leading to the development of a Cost Estimate. The focus of the research is on the application of the tools and techniques that are part of the cost definition process. Consideration is given to what methodology is applied for the development of a Cost Estimate. Purpose – This research aims to document the current status of Project Cost Estimation within Landsvirkjun. The research also documents best practice in relation to Project Cost Estimation. Approach – To begin with, a literature review was performed where best practice for defining Project Cost was established. The review covered Project Management technics used for Private and Public Project Management. Next, a case study of available documents from Landsvirkjun was performed. It was intended to explain how cost estimation was performed by the company. Finally, another case study was performed were the subject for review was Small Hydropower Plant projects. The case study finding helped document current definitions and main cost elements of such projects. Findings – Regarding Landsvirkjun, it was concluded that more information was needed to make any definite conclusions regarding the management of project in connection to cost estimation. However it was possible to state what methods were applied to estimate cost, as well as issues regarding the WBS, Risk Management and contingency were identified. For Small Hydropower Plants (SHP), the definition of such project was clarified and as a result a classification system for SHP projects in Iceland was proposed. The main cost elements of SHP project were also discussed and the main categorise identified. Finally a CBS for small hydro was proposed. Key words – Landsvirkjun/ Energy Framer/ Cost Estimation/ WBS/ Contingency.